A novel method of immunomodulation of endothelial cells using Streptococcus pyogenes and its lysate - Arokiaraj, Mark Christopher; Wilson, Jarad (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
Introduction. Coronary artery diseases and autoimmune disorders are common in clinical practice. Aim. In this study, Streptococcus pyogenes and its lysate were studied to modify the endothelial function. Material and methods. HUVEC cells were seeded in the cell culture, and Streptococcus pyogenes were added to the cell culture, and the supernatant was studied for the secreted proteins. In the second phase, the bacterial lysate was synthesized, and the lysate was added to cell culture and studied. Results. When S. pyogenes alone was added to culture, E Cadherin, Angiostatin, EpCAM and PDGF-AB were some of the biomarkers elevated significantly. HCC1, IGFBP2 and TIMP were some of the biomarkers which showed a reduction. When the lysate was added, the cell-culture was maintained for a longer time, and it showed the synthesis of immune regulatory cytokines. Heatmap analysis showed a significant number of proteins/cytokines concerning the immune/pathways, and toll-like receptors superfamily were modified. BLC, IL 17, BMP 7, PARC, Contactin2, IL 10 Rb, NAP 2 (CXCL 7), Eotaxin 2 were maximally increased. By principal component analysis, the results observed were significant. Conclusion. There is potential for a novel method of immunomodulation of the endothelial cells, which have pleiotropic functions, using S. pyogenes and its lysates.
Keywords: biomarkers; endothelial cells; immune-regulation; Streptococcus pyogenes